A multicenter study of β-lactamase-producing Klebsiella pneumoniae isolated from university teaching hospitals of Urmia, Iran - Darabi, Narges; Motazakker, Morteza; Khalkhali, Hamid Reza; Yousefi, Saber (The Journal of Infection in Developing Countries, 2019)
Introduction: Klebsiella pneumoniae is an opportunistic pathogen accounting for 5-7% of hospital acquired infections. The emergence of carbapenem-resistant Klebsiella pneumoniae has been increasing rapidly over recent years causing many therapeutic problems worldwide. This study aimed to research the antimicrobial resistance profile, detect β-lactamase genes among clinical isolates of K. pneumoniae, and determine their clonal relatedness. Methodology: All Klebsiella pneumoniae isolates were obtained from teaching hospitals in Urmia, Iran. Antimicrobial susceptibility testing was done by the disk diffusion method. Furthermore, minimum inhibitory concentrations of imipenem were determined by applying Etest strips. Screening of β-lactamase-producing isolates was performed by the combined disk method and modified Hodge test. The detection of β-lactamase genes was conducted by polymerase chain reaction (PCR), and isolates’ clonal relatedness was evaluated by random amplified polymorphic DNA (RAPD)-PCR. Results: Overall, 45 out of 182 (24.7%) K. pneumoniae isolates were non-susceptible to imipenem. The combined disk method and modified Hodge test revealed that 93.3% and 71.1% of the imipenem non-susceptible isolates were β-lactamase producers, respectively. The presence of blaVIM, blaNDM, blaKPC, and blaIMP genes was confirmed in 48.9%, 15.6%, 11.1%, and 6.7% of the β-lactamase-producing isolates, respectively. RAPD-PCR revealed that 73% of these isolates were classified into six different clusters. Conclusions: A relatively high prevalence of β-lactamase genes was seen among multidrug-resistant isolates of K. pneumoniae. Most patients infected with β-lactamase-producing isolates had a history of long-term hospitalization and nosocomial infections. The predominance of β-lactamase genes in intensive care unit and internal units alarm clinicians to the growth of hospitalization and mortality rates.